XBP1 increases transactivation of somatic mutants of ESR1 and loss of XBP1 reverses endocrine resistance conferred by gain-of-function Y537S ESR1 mutation. Issue 10 (October 2020) - Barua, David; Abbasi, Benazir; Gupta, Ananya; Gupta, Sanjeev
Abstract: Somatic mutations of the estrogen receptor 1 gene (ESR1) is an emerging mechanism of acquired resistance to endocrine therapy in hormonal breast cancers. Hotspot point mutations in the ligand- binding domain of estrogen receptor α (ER) and genomic rearrangements producing ESR1 fusion genes are the two major types of mutations that are associated with endocrine resistance. The crosstalk between X-box binding protein 1 (XBP1), a key transcription factor of the unfolded protein response (UPR) and ER signalling creates a positive feedback loop that results in increased expression of XBP1 in ER-positive breast cancer. Here we report that XBP1 co-operated with point mutants (Y537S, D538G) and fusion mutants (ESR1-YAP1, ESR1-DAB2) of ESR1 to increase their transcriptional activity. XBP1 was required for optimal expression of estrogen-regulated genes, and up to 40% of XBP1-dependent genes were estrogen-responsive genes. Knockdown of XBP1 in genome-edited MCF7 cells expressing Y537S mutant reduced their growth, re-sensitized them to anti-estrogens and attenuated the constitutive and estrogen-stimulated expression of estrogen-regulated genes. Our study provides a rationale for overcoming endocrine resistance in breast cancers expressing ESR1 mutation by combining the XBP1 targeting agents with anti-estrogen agents. Abstract : Cell biology; Transcriptomics; Biochemistry; Molecular biology; Cancer research; ESR1 mutations, Endocrine resistance, XBP1, ER-Positive breast cancer